Comparison of Serum Iron and Total Iron Binding Capacity Between Hemo and Peritoneal Dialysis Patients - Ali, B.H; Al-Mashadani, Z.I (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, 20 patients were selected having renal failure .10 patients were hemo& 10 peritoneal dialysis procedure. Patients had been given r HuEPO subcutaneous with supplement of Iron dextran after di alysis . Hemoglobin Hb concentration Hematocrit(Hct),serum I ron ,total Iron binding capacity, transferrin saturation percent Ts% & Serum ferritin were measured. Non significant changes in hemoglobin, hematocrit, serum Iron ,totallron binding capacity ,transferrin saturation but a significant difference in serum ferritin was found ,this was a cribed to : 1- The blood lost i n the peritoneal or hemodialysis for access . 2- Some patients had been given blood to treat anemia or given Iron supplements which leads to Iron overload.